PRE-SERVICE TEACHERS’ PERCEPTIONS TOWARDS THE USE OF CANVA IN DESIGNING INFOGRAPHICS AT UNIVERSITY IN CIREBON - Lerianis, Siera; Herawan, Endang (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
Based on a review of the literature, this study intends to give perspectives on the use of infographics in addressing educational requirements. The researchers monitored the participants, mainly the pre-service teachers of the PPG Prajabatan programme at one of Cirebon's universities, who created infographics for their assignments using the Canva design tool. In addition to its aim, this study employed a qualitative descriptive design. Questionnaires were used to gather data for this investigation. It was conducted using a questionnaire-based research design. Twenty pre-service teachers were participating. The researcher investigated ten statement surveys of pre-service instructors' perceptions of using Canva as a medium for generating infographics at a university in Cirebon and found good results. This study concludes on the utilization of Canva as a media tool for designing or generating anything, such as infographics. The findings revealed that pre-service teachers believe Canva may impact focus and creativity while creating infographics. The pre-service teacher appears to be really interested in making infographics using Canva, and they become more creative as a result.